THE USE OF EVEROLIMUS IN KIDNEY TRANSPLANTATION FROM EXPANDED CRITERIA DONORS - I. V. Ulyankina; O. N. Reznik; Y. G. Moysyuk (Вестник трансплантологии и искусственных органов)
The article reflects the use of special schemes of immunosupression in recipients who received kidneys from expanded criteria donors. The reduction of traditional doses of cyclosporine A is discussed in old patients. The data of literature is reviewed about immunosupression schemes including inhibitors of proliferative signal, especially everolimus.